2020
DOI: 10.3390/jcm9123848
|View full text |Cite
|
Sign up to set email alerts
|

Association between Primary Perioperative CEA Ratio, Tumor Site, and Overall Survival in Patients with Colorectal Cancer

Abstract: There are differences in the incidence, clinical presentation, molecular pathogenesis, and outcome of colorectal cancer (CRC) based on tumor location. Emerging research suggests that the perioperative carcinoembryonic antigen (CEA) ratio (post-op/pre-op CEA) is a prognostic factor for CRC patients. We aimed to determine the association between CEA ratio, tumor location, and overall survival (OS) among patients with CRC. We analyzed 427 patients who underwent resection for CRC at the University of Kansas Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…According to the data of 414 patients, the OS and diseasefree survival (DFS) was found to be lower in RCC patients compared to LCC [15]. Similarly to our results, a study with 427 patients found no difference in OS comparing the rightand left-sided colorectal cancer, and there was a significantly higher OS among patients with low CEA values [16]. In a study published in 2020, the authors also did not observe differences in overall, disease-specific, or relative survival in patients with RCC versus LCC [17].…”
Section: Discussionsupporting
confidence: 85%
“…According to the data of 414 patients, the OS and diseasefree survival (DFS) was found to be lower in RCC patients compared to LCC [15]. Similarly to our results, a study with 427 patients found no difference in OS comparing the rightand left-sided colorectal cancer, and there was a significantly higher OS among patients with low CEA values [16]. In a study published in 2020, the authors also did not observe differences in overall, disease-specific, or relative survival in patients with RCC versus LCC [17].…”
Section: Discussionsupporting
confidence: 85%
“…Serum proteins have been used as diagnostic and prognostic markers for cancers for more than thirty years [ 20 ]. As an auxiliary means, serum protein improves the accuracy of diagnosis, such as CEA for colorectal cancer [ 21 ]. However, to our knowledge, no previous studies have shown the diagnostic or prognostic roles of serum SLC3A2 in lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer morbidity ranks third among malignancies, but second in terms of mortality (Sung et al, 2021). Carcinoembryonic antigen (CEA) is used as an important indicator for the diagnosis, treatment, recurrence, and metastasis of CRC (Konishi et al, 2018;Odeny et al, 2020). Additionally, CEA was also associated with other tumors, such as lung cancer (Grunnet and Sorensen, 2012), breast cancer (Tang et al, 2016), and pancreatic cancer (Xing et al, 2018).…”
Section: Introductionmentioning
confidence: 99%